TRADISI SIGAJANG LALENG LIPA’ PERSFEKTIF HUKUM NASIONAL DAN HUKUM ISLAM - Norfazilah; Zulfia Adelia; Anugrah Ramadhani (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
This research explores the Bugis customary law tradition, Sigajang Laleng Lipa', from the perspective of national and Islamic law. This tradition is used as a last resort in conflict resolution through duelling inside the sarong. The aim of this research is to fill the gap of previous studies by focusing on prevention strategies from the perspective of national and Islamic law. The research method is descriptive-analytical qualitative with document analysis. The results show that Sigajang Laleng Lipa' contradicts Indonesian positive law that prohibits physical violence, as well as being incompatible with Islamic law that encourages peaceful dispute resolution. This research contributes by identifying prevention strategies through law enforcement, apparatus training, socialisation, and strengthening the value of peace in Islam. The novelty of this research lies in the integration of national and Islamic legal perspectives to prevent the return of this tradition. The results are expected to provide an understanding of the synergy between national and Islamic law in preserving cultural values while upholding justice and peace.